Perché leggere i filosofi se siamo cristiani? l'"entretien" tra Sacy e Pascal - D'Agostino, Simone 1968- (2025)
Against the background of St. Augustine's complex relationship with various philosophies, as well as of the polemic ignited by Jansenius against philosophy, qua "mother of errors," the confrontation between M. de Sacy and Blaise Pascal, as reconstructed by Nicolas Fontaine in the famous Entretien (1728, 1736), revolves around the question whether Christians still ought to read philosophers - a burning question for the solitaires at Port-Royal. Although Fontaine endeavors to reconcile the two interlocutors' positions, his text reveals both Sacy's concern to avoid any "danger" in reading philosophy and Pascal's attempt at working out a solution. In remarkably medical terms, Pascal suggests "advising" and "regulating" philosophical readings by taking into account each individual's own "conditions" and "customs." Pitting as opposite toxins the reading of the Stoic Epictetus and that of the "skeptical" Montaigne, Pascal's therapy does not propose to mix them but rather to calibrate the dosage of one or the other in order to "counter" each individual's vicious tendencies.
Keywords: Blaise Pascal; Lemaistre de Sacy; Augustine of Hippo; Philosophy